2018
DOI: 10.1007/s10482-018-1061-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 1-aminocyclopropane-1-carboxylate deaminase and d-cysteine desulfhydrase genes among type species of the genus Methylobacterium

Abstract: The presence of 1-aminocyclopropane-1-carboxylate (ACC) deaminase determines the ability of bacteria to increase the resistance of plants to various types of stress. The genes of ACC deaminase (acdS) and the closely related enzyme D-cysteine desulfhydrase (dcyD) were searched in type strains of various representatives of the genus Methylobacterium. Using PCR screening and in silico searching in the available complete genome sequences of type strains, the genes were found in 28 of 48 species of the genus. Phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Bacterial 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (AcdS) is involved in lowering ethylene levels in plants. The importance of bacterial D-cysteine desulfhydrase (DcyD), which is structurally homologous to ACC deaminase, is unknown, but it may be involved in the production of hydrogen sulfide, which also stimulates plant growth ( Ekimova et al, 2018 ). Our analysis showed that acdS was found in clades A and C but not in clade B. dcyD was found mostly in members of clades B and B2 and in a few members of clade A but not in clade C. The chitinase gene was found in a few strains in clade A, while the pectinase gene was found in a few strains in clade B.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (AcdS) is involved in lowering ethylene levels in plants. The importance of bacterial D-cysteine desulfhydrase (DcyD), which is structurally homologous to ACC deaminase, is unknown, but it may be involved in the production of hydrogen sulfide, which also stimulates plant growth ( Ekimova et al, 2018 ). Our analysis showed that acdS was found in clades A and C but not in clade B. dcyD was found mostly in members of clades B and B2 and in a few members of clade A but not in clade C. The chitinase gene was found in a few strains in clade A, while the pectinase gene was found in a few strains in clade B.…”
Section: Resultsmentioning
confidence: 99%
“…With an increasing number of genome sequences available, it became evident that gene products from bacteria (Ekimova et al, 2018) and from plants with high similarity to ACC deaminases exist. However, they are inactive with ACC, but have d -cysteine desulfhydrase activity (DCS).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ACC deaminase activity is not limited to the PGPB that occupy the rhizospheres of obviously stressed plants. Rather, it has been found in α, β, and γ Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes, Archaea, various fungi, and yeast [ 13 , 82 ].…”
Section: Acc Deaminasementioning
confidence: 99%